Comparative immunohistochemical characteristics of expression of estrogen receptors-alpha, progesterone receptors, p16, p53, Ki-67 and caspase 3 in invasive endometrial adenocarcinoma and normal proliferative endometrium - V. A. Tumanskiy; A. V. Chepets (Zaporozhye State Medical University, 2016)
Endometrial cancer occupies the sixth place among newly diagnosed neoplasms in women. In late stage it has unpredictable prognosis. Immunohistichemical studies of the tumor are very important for prognosis of tumor course. The aim. To characterize the expression of the estrogen receptors-alpha, progesterone receptors, p53, p16, ki-67 and caspase 3 in the invasive endometrioid endometrial adenocarcinoma compared with the normal proliferative endometrium. Materials and methods. The uteruses of 56 women with the verified diagnosis of endometrial cancer (stage pT1-4MxNx) and biopsies of 30 women with normal proliferetive endometrium were analyzed. For this purpose, immunohistochemical and morphometrical studies were used. Results: It was established that level of expression of estrogen receptors-alpha was significantly lower in tumor glands and stroma compared with normal proliferative endometrium: the median was 6.0 (5.0; 7.0) points for tumor glands and 7.0 (6.0; 8.0) points for glands of normal proliferative endometrium(р<0,05); for stromal compartment medians were 5.0 (4.0; 6.0) points and 7.0 (6.0; 7.0), respectively (р<0.05). The level of expression of progesterone receptors showed the similar pattern and also was significantly lower in tumor glands and stroma compared with normal tissue. Medians were 7.0 (6.0; 8.0) points for tumor glands and 8.0 (7.0; 8.0) points for normal proliferative endometrium (р<0.05). Medians of expression of progesterone receptors in stroma were 6.0 (4.0; 6.0) points for tumor and 7.0 (7.0; 7.0) for normal endometrial tissue (р<0.05). The distinctive feature of endometrial adenocarcinoma was significantly higher ratio of expression of estrogen receptors-alpha and progesterone receptors in tumor glands and stroma (medians were 1.17 and 1.33, respectively) compared with normal proliferative endometrium (medians for glands and stroma were the same and equaled 1.00). Also it was shown that levels of expression of Ki-67 (the median was 2.0 points), p53 (the median - 11.50%), p16 (the median - 57.08 CUOD) were statistically significantly higher and caspase 3 expression level was statistically significantly lower (the median - 48.54 CUOD) in cells of adenocarcinoma of endometrium compared with normal proliferative endometrium, where the medians for these markers were as follows: the median for Ki-67 was 1.0 point, p53 - 3.00%, p16 - 33.46 CUOD and caspase 3 - 65.02 CUOD. In the stromal component of tumor medians of expression of p16 and caspase 3 were 3.22 and 43.87 CUOD. This was statistically significantly lower than in normal endometrial tissue (the median for p16 - 10.33 CUOD and for caspase 3 - 53.50 CUOD, respectively). Conclusions. Invasive endometrioid adenocarcinoma of the endometrium loses the sensitivity of tumor glandular and stromal cells to harmonizing regulatory signals of estrogen and progesterone in comparison with normal proliferative endometrium. Endometrioid adenocarcinoma has increased expression levels of p53 and p16, elevated level of proliferation and a reduced level of apoptosis of tumor cells compared to cells of normal endometrium.